Gender Equality in Islamic Education: Realizing Inclusivity in ‎Lampung's Multicultural Society - Hikma Apriyani; Muhammad Eko Juliansah; Heny ‎ Wulandari; Nilawati ‎ Tajudin; Chairul Amriyah (IAIN Batusangkar, 2025)
This study explores the implementation of gender equality in Islamic education within the multicultural context of Lampung, Indonesia, examining how gender-sensitive practices are integrated into Islamic educational settings. Using a mixed-methods approach, the research combines quantitative surveys with qualitative interviews to assess gender equality awareness among teachers and students in 10 Islamic schools across Lampung. The findings indicate that while awareness of gender equality is moderate, significant cultural and religious barriers persist, hindering the full implementation of gender-sensitive educational practices. The study highlights the gap between national policies on gender equality and their inconsistent application in rural and conservative regions, where traditional gender roles are deeply ingrained in educational practices. Additionally, the research identifies opportunities for change through targeted teacher training programs and policy reforms that address both gender equality and cultural diversity. The theoretical framework integrates feminist educational theory, which critiques patriarchal interpretations of religious texts, and multicultural education theory, which advocates for inclusive educational environments that respect cultural differences. This research contributes to the ongoing discourse on gender equality in education, providing valuable insights into the complexities of implementing gender-sensitive education in Islamic institutions, particularly in multicultural and conservative contexts like Lampung. The study calls for further research to explore the long-term impact of gender-sensitive education and to incorporate a broader range of stakeholders, including policymakers and community leaders, in future interventions.